Assessing Barriers and Facilitators to Participation in a Nurse-Driven, Opt-Out HIV Screening Program in the Emergency Department - Montgomery, Jackson M. C.; Bouris, Alida; Stanford, Kimberly A. (Global qualitative nursing research, 2024)
Emergency department (ED) HIV screening is a key component of the strategy to end the HIV epidemic, reaching populations with limited access to care for screening and early diagnosis. Many screening programs rely primarily on participation from ED nurses; however, little is known about the factors affecting nurse participation in screening. Guided by the Consolidated Framework for Implementation Research, 20 semi-structured interviews were conducted with ED nurses to explore perceptions of HIV screening, barriers and facilitators to participation, and implementation insights. Nurses were categorized as either high adopters or low adopters based on the number of HIV tests ordered 3 months prior to interviews. The Stanford Lightning Report Method, a rapid qualitative analysis approach, was used to analyze field notes. All participants generally agreed that the ED was an appropriate location for screening and that frequent, multimodal education about screening was needed. Integration of screening into standard workflows, education about the public health impact of screening, and the use of peer champions and mentors were identified as important strategies to increase participation. By incorporating these findings into implementation strategies, EDs may be able to increase nurse participation in screening, addressing important health equity issues in HIV diagnosis.